Health worker remuneration in WHO member states (2013)
Presents the available data on the money spent by WHO Member States on remunerating health workers in the public and private sectors. Concludes that as they seek to attain universal health coverage (UHC), countries will need to devote an increasing proportion of their GDPs to health and health worker remuneration.
Keywords: HEALTH SERVICES